AmruthMune, A Standardized Extract Comprises of Tinosporin from Tinospora cordifolia and its Mechanism of Immunostimulatory Activity - Gouthamchandra, Kuluvar; Venkataramana, Sudeep Heggar; Amritharaj, Amritharaj; Sathish, Anusha; Basavegowda, Lingaraju Harakanahalli; Puttaswamy, Naveen; Kodimule, Shyam Prasad (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Tinospora cordifolia is an illustrious medicinal herb in Indian traditional ayurvedic medicine because of its substantial medicinal properties. It is reported that Tinospora cordifolia has been used to cure for many ailments by traditional medicinal practitioners. It is captivating that, in this contemporary world Tinospora cordifolia is being used to retain good immune health. Materials and Methods: The objective of this research is to demonstrate the immune enhancing activity of AmruthMune a standardized extract of T. cordifolia extract with Tinosporin. MTT assay, NO assay, H2 O2 assay, Phagocytosis assay, ELISA, and western blotting experiments were conducted in this study to understand the efficacy and its basic molecular mechanism. Results: Quantitative HPLC analysis determined that the AmruthMune a standardized Tinospora cordifolia extract comprise of active principle Tinosporin (1%). In addition, AmruthMune treatment dramatically improved the phagocytosis and secretion of H2 O2 NO, TNF-α, and IL-6 in macrophage cells. Furthermore, consequences of western blot experiments demonstrated that AmruthMune treatment activates p-ERK, p-p38 and p-JNK. Conclusion: Collectively, these results exhibited MAPK signalling pathway involved in AmruthMune elicited macrophage activation and it could be a promising functional food in immune modulation.
Keywords: Immune modulation; Murine macrophages; Phagocytosis; ELISA; MAPK signalling; pathway